2015
DOI: 10.1200/jco.2014.57.4111
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Consumption and Risk of Cutaneous Malignant Melanoma

Abstract: Purpose Citrus products are widely consumed foods that are rich in psoralens and furocoumarins, a group of naturally occurring chemicals with potential photocarcinogenic properties. We prospectively evaluated the risk of cutaneous malignant melanoma associated with citrus consumption. Methods A total of 63,810 women in the Nurses' Health Study (1984 to 2010) and 41,622 men in the Health Professionals Follow-Up Study (1986 to 2010) were included. Dietary information was repeatedly assessed every 2 to 4 years du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
4
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 33 publications
4
75
4
3
Order By: Relevance
“…For example, PGC-1β polymorphisms have been associated with tanning ability and melanoma susceptibility, which along with basic science data supported the regulatory role of PGC-1 coactivators in human tanning. 45 Following our epidemiologic findings on citrus consumption and melanoma, 37 further research into furocoumarin levels in citrus fruit and juice and participants' blood samples is in progress to confirm the photocarcinogenesis hypothesis.…”
Section: Major Challenges and Ongoing Effortsmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, PGC-1β polymorphisms have been associated with tanning ability and melanoma susceptibility, which along with basic science data supported the regulatory role of PGC-1 coactivators in human tanning. 45 Following our epidemiologic findings on citrus consumption and melanoma, 37 further research into furocoumarin levels in citrus fruit and juice and participants' blood samples is in progress to confirm the photocarcinogenesis hypothesis.…”
Section: Major Challenges and Ongoing Effortsmentioning
confidence: 91%
“…37 The association appeared strongest for grapefruit. Consistent with a potential synergistic effect between psoralens and UV radiation, the association appeared to be stronger among those with a higher susceptibility to sunburn as a child or adolescent, those with more blistering sunburns, and those who spent more time in direct sunlight.…”
Section: Skin Cancermentioning
confidence: 99%
“…Epidemiologic studies in recent years have reported that associations between skin cancer risk and a number of other environmental factors besides sun exposure either may have protective (eg, caffeine) or potentiate (eg, citrus products) effects on the incidence of skin cancer (14)(15)(16)(17). However, little is known about whether these potential skin cancer risk factors may modify the relationship between KC history and melanoma.…”
mentioning
confidence: 96%
“…Information on dietary factors, including consumption of citrus products, alcohol, and coffee, was repeatedly collected using a validated food frequency questionnaire at least every four years during the follow-up (17). Data on the following phenotypic and sun exposure-related factors were also collected in the follow-up questionnaires: ethnicities; family history of melanoma in first-degree relatives (parents, siblings, or offspring); natural hair color at an early age (age 21 years in NHS, and age 18 years in NHSII/HPFS); number of moles on extremity (arms in NHS/HPFS and legs in NHSII); skin reaction after prolonged sun exposure as a child/adolescent; number of severe or blistering sunburns; average time spent in direct sunlight in summer months since high school; regular use of sunscreen in summer months; and cumulative UV flux since baseline (a measure of long-term UV exposure) (14,17,21).…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…PUVA therapy (oral Psoralen with UVA light radiation), is a very effective treatment for psoriasis, but in rare instances it can contribute to the development of melanoma . Psoralen is a furanocoumarin and sensitizes the skin to UV light exposure . Citrus fruits are high in Vitamin C, which is necessary for collagen synthesis and wound healing, and have been shown to have other benefits including neuroprotection, improvement in lipid profiles and inflammatory markers, reduction of cardiovascular risk, and serve as a rich source of antioxidants .…”
mentioning
confidence: 99%